MAKNA KEMISKINAN DAN PENANGGULANGAN YANG DIBUTUHKAN MENURUT ORANG MISKIN - Arif Sofianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2013)
This study attempts to answer questions about: 1). How the meaning of poverty for poor people themselves, and how to understand why someone is poor, and 2). What policies had done to tackle poverty and how much success. This study used a qualitative approach. The location of this research is the Brebes Regency, Cilacap Regency and Wonosobo Regency. This study concludes that: 1). Poverty is defined as absolute poverty is the lack of income to make ends meet, the lack of ownership of resources and structural perspective is very limited access to jobs, capital, skills. 2). Various poverty alleviation programs and activities are less touched on the poor, many poverty alleviation activities enjoyed by not poor.